Kontribusi Kegiatan Bahtsul Masail dalam Meningkatkan Kemampuan Memahami Kitab Kuning dan Berfikir Kritis Santri di Forum Musyawarah Anjang Sana Anjang Sini (FMAA) di Kabupaten Jember - Helmi, Achmad Mahrus; Hanifuddin, Hanifuddin (LP. Ma'arif Janggan Magetan, 2023)
This research aims to determine: (1) Implementation of bahtsul masail activities in FMAA activities (2) Contribution of FMAA activities in increasing students' understanding of the yellow book. (3) Contribution of FMAA activities in improving Santri's critical thinking. (4) Supporting and inhibiting factors for FMAA's contribution to increasing students' understanding of the yellow book and students' critical thinking. The method used is field research with a qualitative approach and the type of research is case study. Data collection uses interview, observation and documentation methods. The data analysis techniques used are: data reduction, data presentation, and drawing conclusions. The results of the research show that bahtsul masail activities in the Anjang Sanjang Here (FMAA) deliberative forum can contribute to increasing the understanding of Santri in understanding the Yellow Book and thinking critically.